Correction: The effect of poor vision on economic farm performance: Evidence from rural Cambodia. - Frederik Sagemüller; Selina Bruns; Oliver Mußhoff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274048.].